PROSES PRODUKSI VOICE OVER KONTEN BERITA PENDEK SELEBRITIS DI YOUTUBE TRIBUN SUMATERA SELATAN - Amanda Anggun Shalihah,; Isnawijayani, Isnawijayani; Desy Misnawati,; Leo Ferdian Fauzi4, (Journal of Innovation Research and Knowledge, 2025)
This study discusses the process of producing celebrity news through voice over in short video content on the YouTube channel of Tribun Sumatera Selatan. The research uses a qualitative approach with descriptive methods. Data collection techniques were carried out through interviews, observations, and documentation. The results showed that the production process involves planning, scripting, voice over execution, video editing, and publication. The voice over technique used plays a significant role in delivering the information clearly and engagingly. The study also highlights the consistency and quality of the voice over, and how audiences respond to the news content